Assessment of Moisture Susceptibility for Asphalt Mixtures Modified by Carbon Fibers - Huda Qasim Mawat; Mohammed Qadir Ismael (Salehan Institute of Higher Education, 2020)
Moisture induced damage in asphaltic pavement might be considered as a serious defect that contributed to growth other distresses such as permanent deformation and fatigue cracking. This paper work aimed through an experimental effort to assess the behaviour of asphaltic mixtures that fabricated by incorporating several dosages of carbon fiber in regard to the resistance potential of harmful effect of moisture in pavement. Laboratory tests were performed on specimens containing fiber with different lengths and contents. These tests are: Marshall Test, the indirect tensile test and the index of retained strength. The optimum asphalt contents were determined based on the Marshall method. The preparation of asphaltic mixtures involved three contents of carbon fiber namely (0.10%, 0.20%, and 0.30%) by weight of asphalt mixture and three lengths including (1.0, 2.0 and 3.0) cm. The results of this work lead to several conclusions that mainly refer to the benefits of the contribution of carbon fibers to improving the performance of asphalt mixtures, such as an increase in its stability and a decrease in the flow value as well as an increase in voids in the mixture. The addition of 2.0 cm length carbon fibers with 0.30 percent increased indirect tensile strength ratio by 11.23 percent and the index of retained strength by 12.52 percent. It is also found that 0.30 % by weight of the mixture is the optimum fiber content for the three lengths.